Impactful Research on Transformational Information Technology: An Opportunity to Inform New Audiences1 - Lucas, Henry C.; Agarwal, Ritu; Clemons, Eric K.; El Sawy, Omar A.; Weber, Bruce (MIS Quarterly, 2013)
Information technology has arguably been one of the most important drivers of economic and social value in the last 50 years, enabling transformational change in virtually every aspect of society. Although the Information Systems community is engaged in significant research on IT, the reach of our findings may be limited. In this commentary, our objective is to focus the IS community’s attention on the striking transformations in economic and social systems spawned by IT and to encourage more research that offers useful implications for policy. We present examples of transformations occurring in four distinct sectors of the economy and propose policy-relevant questions that need to be addressed. We urge researchers to write papers based on their findings that inform policy makers, managers, and decision makers about the issues that transformational technologies raise. Finally, we suggest a new outlet to publish these essays on the implications of transformational informational technology.